2022
DOI: 10.1364/oe.458412
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional analysis and verification of lightning-type electromagnetic metasurfaces

Abstract: Aiming at the problems that most of the existing electromagnetic metasurfaces have single function and narrow application scope, a highly integrated lightning-type metasurface is proposed in this study. It can realize the functions of circular dichroism (CD), absorption of electromagnetic waves, broadband x-to-y cross polarization conversion (CPC) function, linear-to-circular polarization conversion (LTC-PC) function and asymmetric transmission (AT), and its functions are also analyzed and verified. The design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…This causes LCP waves to be reflected and RCP waves to be absorbed, ultimately giving rise to CD. 12…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This causes LCP waves to be reflected and RCP waves to be absorbed, ultimately giving rise to CD. 12…”
Section: Resultsmentioning
confidence: 99%
“…In this context, E f for the top square graphene resonant ring is denoted as E f1 , while the middle N-type graphene layer's E f is designated as E f2 . The electrical conductivity of graphene is described using the Drude model, as expressed in eqn (2): 12 In the equation, ω is the angular frequency, μ c is the Fermi energy level, Γ is the scattering rate, k B is Boltzmann's constant, ħ is the reduced Planck constant, and e is the electronic charge. In this paper, the graphene temperature is set to T = 300 K, and the relaxation time τ = 1 ps.…”
Section: Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that the optical switch that enables the signal to be turned on and off by another controller plays an important role in routing the optical signal in optical communication and information processing [ 49 ]. However, the prevailing way of optical switching usually requires an auxiliary power supply and additional control circuits that are physically connected to the metasurface, thus leading to increasing the size of the system and inducing needless cross-talk [ 50 , 51 ].…”
Section: Results and Discussionmentioning
confidence: 99%